Tm-Doped Fiber Laser Cladding Pumped by a Pulsed Er-Doped Fiber Laser with a 110 μm Core - Aleksandr Khegai; Sergei Firstov; Konstantin Riumkin; Denis Lipatov; Mikhail Melkumov (Photonics)
Pulsed laser sources operating in the spectral range of 1.8 to 2.1 μm draw considerable attention due to their wide range of practical applications in many areas, including medicine, sensing, materials processing, etc. In this work, we propose a pulsed Tm-doped fiber laser scheme operating in the 2 μm spectral region with pulsed pumping at 1.57 μm. The pump source consisted of a series-connected Er-Yb pulsed master oscillator and an EDFA emitting ∼400 μs pulses with an energy of 9.3 mJ. Using this setup, we made a Tm-doped fiber laser that provided 2 mJ pulses in the 2 μm spectral region with a slope efficiency of 28% from pulses at 1.57 μm.